Dynamic Reconstruction of Anal Sphincter with Camera Shutter Style Double-Opposing Gracilis Flaps - Wong, Allen Wei-Jiat; Tan, Grace Hui-Min; Koh, Frederick Hong-Xiang; Chew, Min Hoe (Archives of Plastic Surgery, 2023)
Fournier's gangrene is a life-threatening infection which requires prompt recognition, early surgical debridement of unhealthy tissue, and initiation of broad-spectrum antibiotics. Relook debridement are usually performed until all the devitalized tissue has been removed. Involvement of the anal sphincter may result in significant morbidity such as permanent incontinence. Dynamic reconstruction of the anal sphincter has always been one of the holy grails in the field of pelvic reconstruction.We demonstrate a new method of camera shutter style double-opposing gracilis muscle flaps that allows dynamic sphincteric function without the need for electrostimulation. The bilateral gracilis muscles are inset in a fashion that allows orthograde contraction of the muscle to narrow and collapse the neoanal opening. With biofeedback training, the patient is able to regain dynamic continence and return to function without a stoma. There was also no need for neurotization or microsurgery techniques to restore sphincteric function to the anus. The patient was able to reverse his stoma 14 months after the initial insult and reconstruction with biofeedback training without the use of electrostimulation.
Keywords: Fournier's gangrene; gracilis muscle; dynamic sphincter; anal sphincter reconstruction